Influences of number of adults and adult: child ratios on the quantity of adult language input across childcare settings. Issue 6 (December 2018) - Soderstrom, Melanie; Grauer, Elizabeth; Dufault, Brenden; McDivitt, Karmen
New approaches to examining the language environment are putting greater emphasis on the use of highly naturalistic audio recordings and questions about cross-cultural differences in children's real-world language experiences. These new approaches and questions require careful examination of different kinds of variables that may influence children's language experiences. The current study examines the influence of the number of adults and adult:child ratio on the number of words heard by young children across three childcare settings (home, home daycare and daycare centre). The home setting was characterized by a high number of one-on-one interactions, while children in daycare centres were exposed to larger numbers of adults present. While a linear relationship was found between the number/ratio of adults and words heard in the home setting, these relationships were more complex in daycare centres, and no relationships were found in home daycares.